LESSONS OF THE FOREIGN LANGUAGES AND DESIGNING A PECULIAR PLAN IN THE PROCESS OF TEACHING - Boymurodova Feruza Ziyot Kizi; Aripova Matluba Lutfullayevna (International Journal of Innovations in Engineering Research and Technology, 2021)
This article argues about the prestigeof the foreign languages lessons.In particular, this very article concentrates on the various ways of teaching process how it is significantly basic to make peculiar lesson plans. It is undoubtedly true that distinctive features of foreign languagesare extremely appealing to attract language learners or students to dive in studying like a bookworm. Moreover, thisarticle goals at instilling eternal knowledge on the primary steps of lessons. It deals with fruitful information upon the list of core kinds of lessons.